Kinetochore and ionomic adaptation to whole-genome duplication in Cochlearia shows evolutionary convergence in three autopolyploids - Bray, Sian M.; Hämäla, Tuomas; Zhou, Min; Busoms, Silvia; Fischer, Sina; Desjardins, Stuart D.; Mandáková, Terezie; Moore, Chris; Mathers, Thomas C.; Cowan, Laura; Monnahan, Patrick; Koch, Jordan; et al. (Cell reports)
Whole-genome duplication (WGD) occurs in all kingdoms and impacts speciation, domestication, and cancer outcome. However, doubled DNA management can be challenging for nascent polyploids. The study of within-species polyploidy (autopolyploidy) permits focus on this DNA management aspect, decoupling it from the confounding effects of hybridization (in allopolyploid hybrids). How is autopolyploidy tolerated, and how do young polyploids stabilize? Here, we introduce a powerful model to address this: the genus Cochlearia, which has experienced many polyploidization events. We assess meiosis and other polyploid-relevant phenotypes, generate a chromosome-scale genome, and sequence 113 individuals from 33 ploidy-contrasting populations. We detect an obvious autopolyploidy-associated selection signal at kinetochore components and ion transporters. Modeling the selected alleles, we detail evidence of the kinetochore complex mediating adaptation to polyploidy. We compare candidates in independent autopolyploids across three genera separated by 40 million years, highlighting a common function at the process and gene levels, indicating evolutionary flexibility in response to polyploidy.